Evaluating construction project success with use of the M-TOPSIS method - Pinter, Urban; Pšunder, Igor (Journal of Civil Engineering and Management, 2013)
A problematic of construction project success evaluation is discussed in this paper. It is established that the success of a construction project depends on success in achieving goals in different success criteria which may or may not be co-dependent; hence, the calculation of construction project success is a multi-dimensional evaluation problem. Therefore, it is necessary to discuss the overall success of a construction project as a multi-criterion problem that can be solved using a multi-criteria decision method. A new approach to overall construction project success calculation is presented, based on the multi-criteria decision method M-TOPSIS. M-TOPSIS ranks results from ideal solution to negative ideal solution which suitable fits with a presented new approach to generalized project success evaluation method. For an ideal solution, the best values from all considered projects, including pre-production plan parameters, are used, and for negative ideal solution, minimal parameters for each criterion are defined. Because, in civil engineering, projects can be done even better than planned, results from M-TOPSIS are then transposed, so that results are presented on a scale from minimal solution (0) to planned solution (1) and above. Several project successes can be compared with each other and ranked according to their performance with this method. Since results from this method are very sensitive to incorrectly input data, the basic M-TOPSIS method theory is closely, presented and a simple practical example for using the suggested method is also shown.